Medication therapy and treatment goal achievement among persons with coronary heart disease in a general population - Guideline adherence, medication adherence and validation of medication use - Pedersen, Elisabeth (UiT The Arctic University of Norway, 2021)
Aim - To assess the adherence to medication therapy for secondary prevention and achievement of treatment goals in persons with coronary heart disease (CHD) in a general population. Methods - This project used data from the seventh wave of the Tromsø Study, alone and linked with data from the Norwegian Prescription database (NorPD). Participants self-reporting CHD were included (n = 1483). In Paper I, the associations between guideline adherence and achievement of treatment goals were assessed using logistic regression. Paper II validated the self-reported medication use by comparing by it to pharmacy dispensings from NorPD. In Paper III medication adherence was calculated based on pharmacy dispensings from NorPD, and the associations between medication adherence and blood pressure and low-density-lipoprotein (LDL)-cholesterol were explored using linear regressions. Results - Use of lipid-lowering drugs (LLDs) was reported by 76% of the study population, antihypertensive drugs by 72% and acetylsalicylic acid (ASA) by 66%. Agreement between self-reported medication use and pharmacy dispensings was high for all three medication groups (kappa ≥0.61). Average medication adherence (proportion of days covered) was 0.94 for both LLDs and antihypertensive drugs and 0.97 for ASA. The recommended treatment goal for LDL-cholesterol was reached by 9% of the population. Achieving this treatment goal was associated with use of LLDs. Lower LDL-cholesterol was also associated with higher adherence to LLDs. The blood pressure goal was reached by 58% of the population, but achieving this goal was not significantly associated with using antihypertensive drugs. There was also no statistically significant association between adherence to antihypertensive drugs and lower systolic or diastolic blood pressure. Conclusions - Use of and adherence to medications for secondary prevention of CHD was high, but achievement of treatment goals for blood pressure and especially LDL-cholesterol was low. Our results indicate that the ...